The role of project managers in sustainable building process: a study on Malaysian construction industry - Suriani, Mat Noor (2013)
Providing all residences of a community with a better quality of life by developing of environmental, social and economic aspects has been focused in sustainable development for decades. In order to achieve the sustainable development, the construction industry is an important sector that should adopt the sustainability concept. Sustainable construction faces some challenges in adopting new processes and working methods due to the new technologies that require some changes in the process and considering risk. The purpose of this research is to find out the role of project managers in sustainable building process in construction industry. The main things that need to be cover are to identify the challenges in sustainable building process and to investigate the relationship between the role of project managers and the challenges. The challenges will identify in three phases such as feasibility and design phase, bidding phase and construction phase. In order to achieve this purpose, a literature review has been conducted to find out the challenges that face by project managers in the sustainable building process and questionnaire survey will use to investigate the relationship between the role of project managers and the challenges. From the finding and analysis done, the true information about the objective one and objective two can be determine. The result that gets from this finding and discussion is there have six variables that have strong positive relationship between the challenges and the role of project manager. The outcomes present the focuses and process as well as main challenges in sustainable building design and construction. These challenges are presented in a time line of a building process. As a conclusion, project managers can play a vital role in integrating sustainability to a building project during design and construction process to deliver a successful sustainable building. Their role is significant to overcome the challenges in sustainable building process.